ANALYSIS OF VILLAGE FUND ALLOCATION MANAGEMENT (ADD) IN LAMUNRE TENGAH VILLAGE, NORTH BELOPA DISTRICT, LUWU REGENCY - Ilmi, Nur; Jamil, Muh; Irwandi, Irwandi (Jurnal Comparative: Ekonomi dan Bisnis, 2024)
This study aims to determine the management of village fund allocation (ADD) in Lamunre Tengah Village, Belopa Utara District, Luwu Regency. This research method uses qualitative descriptive with data collection using interviews and documents/asrips. The stages of village fund allocation management include Planning, Implementation, Administration, Reporting, Accountability, and Supervision. The results of the study indicate that ADD Management in Lamunre Tengah Village, Belopa Utara District, Luwu Regency has followed the technical instructions set out in the regulations. However, the process is still not optimal, at the planning stage Lamunre Tengah Village has not planned village development. So that the implementation of the use of the ADD budget has not been effective. For ADD reporting in Lamunre Tengah Village is not good due to the lack of participation of other employees to assist in preparing reports and supervision from the Village Consultative Body (BPD) is still not effective due to the lack of understanding related to such as direct superiors regarding the performance of the Lamunre Tengah Village government.